2016
DOI: 10.1007/s11255-016-1408-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the isolation of urinary exosome

Abstract: Acidic environment was likely to conducive to the isolation of exosome and maintain its stability and integrity that suggest pH medium needs to be carefully considered and also provide a methodology for future separation exosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…These different methods may vary in purity of the resulting EVs and in the complexity of the protocol, and therefore in their possible clinical application. To avoid the analysis of urinary contaminants, such as shed cells or unbound proteins, some technical precautions are needed including centrifugations or filtration steps, addition of protease inhibitors, and pH control (Zhou et al, 2006a; Zhao et al, 2017). The advantage of EVs as biomarker is the possibility to obtain different sets of information.…”
Section: Evs As Renal Disease Biomarkersmentioning
confidence: 99%
“…These different methods may vary in purity of the resulting EVs and in the complexity of the protocol, and therefore in their possible clinical application. To avoid the analysis of urinary contaminants, such as shed cells or unbound proteins, some technical precautions are needed including centrifugations or filtration steps, addition of protease inhibitors, and pH control (Zhou et al, 2006a; Zhao et al, 2017). The advantage of EVs as biomarker is the possibility to obtain different sets of information.…”
Section: Evs As Renal Disease Biomarkersmentioning
confidence: 99%
“…However, in this study no information about changes in the particle concentration was reported. Some other studies revealed the effect of pH, storage temperature and cycles of freezing and thawing only on the yield of exosome isolation, but not on quantity changes during storage (Akers et al, 2016;Ban et al, 2015;Zhao et al, 2017). Therefore, the standard criterion of exosomal preservation condition is still undefined.…”
mentioning
confidence: 99%
“…Typically, exosomes are secreted by all cells with a diameter of 30-120nm lipid bilayer membrane and they can be identified in biological fluids including urine, blood, serum and saliva 13 - 17 . Exosomes are small extracellular vesicles with various molecular constituents including proteins, mRNA and microRNA which have the potential to be biomarkers in various malignancies including PCa 18 .…”
Section: Discussionmentioning
confidence: 99%